Heavy metal pollution in the western part of Peshawar metropolis, north Pakistan (Journal of Nepal Geological Society, 1998)
Peshawar is the capital of North-West-Frontier-Province (NWFP) and the largest trade centre in the northwestern part of Pakistan. Due to high rate of urbanisation and the sudden influxes of Afghan refugees in the past two decades, the city has become one of the most polluted ones in the South Central Asia. The increased load of transportation with no or limited expansion of roads, unplanned and uncontrolled industrialisation and poor sanitation have caused the atmosphere unprecedently overburdened with smokes and dusts of all kinds. This paper is a part of a detail study carried out to determine heavy metal concentrations in air dust, soil and sewerage of the Peshawar metropolis.In the western part of Peshawar metropolis at 16 chowks (road crossings), air dust samples were collected at nose height and at ground positions in open buckets filled with distilled water for 48 hours. From the same locations, clay/road-mud samples were collected from solidified clay on ground surface. Similarly, soil samples were collected from non-metalled parts at 2 feet depths in subsurface from 10 locations. Correspondingly, sewerage samples were collected from sewerage water and sewerage mud. Vehicular traffic counting was carried out at each chowk for 12 peak hours. At nose height the heavy metal  contents  showed  ppm ranges of:  Cr=  0.06-3.2, Co=  0.3-2.4,  Ni=  0.17-5.97, Cu=  0.88-8.8, Zn = 0.81-17, Fe = 3-57 and Pb 2-25. The heavy metals concentrations at ground positions were noticed to be higher than at the nose level. The soil samples do not show significant enrichment in heavy metals and are therefore classified as the normal soils. In sewerage water samples the heavy metals concentrations showed ppm ranges of Cr= 0.1-3.81, Co= 0-2, Ni = 0.1 -3, Cu = 0.13-3, Zn = 0.1 - 4.3, Fe = 13 -99 and Pb = 1.81-10. Sewerage mud showed higher concentrations of these metals as compared to sewerage water. A systematic positive variations between the atomic masses of the metals and their concentrations was noticed in air, clay, sewerage water and sewerage mud, indicating that the higher the atomic mass, the higher was the rate of fall/deposition of that particular metal, if available. It was also noticed that compared with water, air is a finer sorting agent for heavy metals.At each chowk, both individual metal and the total dust fall showed positive correlation with the total number of vehicles, indicating that the moving vehicular traffic is the major cause of keeping metals loaded dust in the air. However, these vehicles may not be considered as the major source of emanating these metals from their exhausts. The study showed that the major sources of heavy metals in the western part of Peshawar metropolis are small metal shops, workshops, construction projects, rusted bridges, fences and vehicles on the roads as well as the damaged sewerage system.